Concurrent mycosis fungoides and intravascular large B‐cell lymphoma in a single patient. (3rd April 2020) - Goyal, Amrita; Totoraitis, Kristin; Toama, Wael; He, Fiona; Bohjanen, Kimberly; Williams, Sarah; Miller, Daniel D.
Abstract: Mycosis fungoides (MF) is an indolent, uncommon, non‐Hodgkin T‐cell lymphoma of the skin. It classically presents with patches, plaques, and tumors and may rarely show spread to internal organs or bone marrow. Up to 7.5% of MF patients may be diagnosed with a second malignancy. Intravascular large B‐cell lymphoma (IVLBCL) is an exceedingly rare non‐Hodgkin B‐cell lymphoma characterized by predominant growth of large neoplastic cells in the lumina of blood vessels. This case presents with an unusual confluence of two rare diagnoses, MF and IVLBCL, made more remarkable by the presence of both diagnoses on a single skin biopsy sample.